Color Tuning: Photonic Tuning of the Emission Color of Nanophosphor Films Processed at High Temperature (Advanced Optical Materials 13/2017). Issue 13 (4th July 2017) - Geng, Dongling; Lozano, Gabriel; Calvo, Mauricio E.; Núñez, Nuria O.; Becerro, Ana I.; Ocaña, Manuel; Míguez, Hernán
Abstract : In article number1700099, Gabriel Lozano, Hernán Miguez, and co‐workers explore photonic tuning of the emission color of nanophotonics films. The emission of these GdVO4 :Dy 3+ nanocrystals can be strongly modulated from blue to yellow, using photonic multilayers, in which a transparent and bright nanophosphor film is integrated as an optical dopant. Photonics offers new opportunities to tailor the emission of nanophosphor materials, which can provide benefits to next generation light‐emitting devices.